2010
DOI: 10.1093/bja/aeq185
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base alterations during laparoscopic abdominal surgery: a comparison with laparotomy

Abstract: The decrease in the pH during the pneumoperitoneum was affected by the increase in Pa(CO(2)), which promptly returned to a normal value after the desufflation. On the other hand, the decrease in the pH after laparotomy was affected by the metabolic factors, which persisted an hour after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Sample size calculation was performed based on a previous study that reported the core body temperature during laparoscopic abdominal surgery with sevoflurane-remifentanil anesthesia [12]: 90% power to detect a mean difference of 0.4℃ in core body temperature between sevoflurane and propofol anesthesia during prolonged pneumoperitoneum with a SD of 0.4℃ and an alpha level of 0.05 using an independent t-test. And, we calculated that 22 patients would be needed in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculation was performed based on a previous study that reported the core body temperature during laparoscopic abdominal surgery with sevoflurane-remifentanil anesthesia [12]: 90% power to detect a mean difference of 0.4℃ in core body temperature between sevoflurane and propofol anesthesia during prolonged pneumoperitoneum with a SD of 0.4℃ and an alpha level of 0.05 using an independent t-test. And, we calculated that 22 patients would be needed in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The carbon dioxide pneumoperitoneum causes an increase in abdominal pressure and carbon dioxide absorption through the peritoneal serosa, which can cause hypercarbia and respiratory acidosis. 7 This patient's morbidity associated with her mesh removal may have been secondary to the prolonged use of the laparoscopic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous study [6], a sample size of 12 patients per group was calculated to demonstrate a mean difference in pH of 0.06 with an expected SD of 0.05, using values of α = 0.05 with a power (1-β) of 80%. In order to compensate for an estimated dropout rate of 25%, 15 patients for each group were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Stewart's physiochemical approach was used to analyze the acid base alteration in this study because the traditional approaches by the Henderson-Hasselbalch equation are often inadequate to explain the complexity of acid-base derangements during laparoscopic surgery [6-8]. …”
Section: Introductionmentioning
confidence: 99%